(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Atopic dermatitis (AD) affects up to 20% of children globally and is the most prevalent chronic inflammatory skin disease in pediatric populations. Its pathogenesis is governed by a bidirectional interaction between innate and adaptive immune dysfunction: keratinocyte-derived alarmins (TSLP, IL-33, IL-25) prime type 2 innate lymphoid cells and Th2 lymphocytes, which produce IL-4, IL-13, IL-31, and IL-5, driving IgE class switching, eosinophilia, barrier disruption, and neurogenic pruritus through JAK1-mediated signaling cascades.